2015
DOI: 10.1158/1535-7163.mct-14-0547
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Hepatic Organic Anion-Transporting Polypeptides to Docetaxel Uptake and Clearance

Abstract: The antimicrotubular agent docetaxel is a widely used chemotherapeutic drug for the treatment of multiple solid tumors and is predominantly dependent on hepatic disposition. In this study, we evaluated drug uptake transporters capable of transporting radiolabeled docetaxel. By screening an array of drug uptake transporters in HeLa cells using a recombinant vaccinia-based method, five organic anion transporting polypeptides (OATPs) capable of docetaxel uptake were identified: OATP1A2, OATP1B1, OATP1B3, OATP1C1,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 44 publications
4
34
0
Order By: Relevance
“…These findings have been independently verified (30)(31)(32)(33)(34), and are consistent with in vitro studies that have identified paclitaxel as a potent inhibitor of OATP1B1-(35, 36) and OATP1B3-mediated transport (35,37,38). However, none of the other known 9 human OATPs or other rodent OATPs are capable of transporting paclitaxel (39), and similar results have been obtained with docetaxel (40). These studies highlight the notion that OATPs capable of transporting paclitaxel need to be expressed in tissues such that the drug can exert cellular injury.…”
Section: Oatp1b2 As a Putative Paclitaxel Transporter In Mouse Neuronssupporting
confidence: 87%
“…These findings have been independently verified (30)(31)(32)(33)(34), and are consistent with in vitro studies that have identified paclitaxel as a potent inhibitor of OATP1B1-(35, 36) and OATP1B3-mediated transport (35,37,38). However, none of the other known 9 human OATPs or other rodent OATPs are capable of transporting paclitaxel (39), and similar results have been obtained with docetaxel (40). These studies highlight the notion that OATPs capable of transporting paclitaxel need to be expressed in tissues such that the drug can exert cellular injury.…”
Section: Oatp1b2 As a Putative Paclitaxel Transporter In Mouse Neuronssupporting
confidence: 87%
“…Consistent with its decreased membrane expression, the 521T>C SNP affected mainly the maximum transport velocity in comparison to substrate affinity . The deleterious functional consequence of the 521T>C variant was confirmed in subsequent studies with a diverse list of OATP1B1 substrates, including rifampin, pravastatin, atorvastatin, rosuvastatin, atrasentan, ezetimibe glucuronide, methotrexate and docetaxel . Another common variant associated with potentially altered transport activity of OATP1B1 is 388A>G (*1b), located in exon 4, but the functional consequences of this variant remain controversial.…”
Section: Slco1b1 Genetic Variabilitymentioning
confidence: 92%
“…MDCKII cells stably expressing single (OATP1B1, OATP1B3 and MDR1) and double (OATP1B1/MDR1 and OATP1B3/MDR1) transporters, including control cells (MDCKII-Co), were generated and characterized previously (Lee et al, 2015). For this study, single (MDCKII-OATP1A2)-and double (MDCKII-OATP1A2/MDR1)transfected cells were also generated using the same methods as conducted previously (Lee et al, 2015). Briefly, both parent MDCKII cells and MDCKII-MDR1 cells were transfected or retransfected with the plasmids pcDNA3.1(1)/OATP1A2 using Lipofectamine 2000 reagent (Invitrogen) according to the manufacturer's instructions.…”
Section: Generation Of Stably Transfected Mdckii-oatp1a2 and Mdckii-omentioning
confidence: 99%
“…Protein expressions from MDCKII-OATP1A2 and -OATP1A2/MDR1 cells, including control cells, were examined by immunoblot analysis of plasma membrane enriched preparations. Crude cell membrane fractions were conducted as described previously with minor modification (Kim et al, 1998;Lee et al, 2015). Briefly, cells were scraped, collected, and homogenized in 5 mM Hepes (pH 7.2) cell lysis buffer containing 1Â protease inhibitor cocktails (Roche).…”
Section: Crude Cell Membrane Fractions and Immunoblot Analysismentioning
confidence: 99%